MULTI-CRITERIA RECOMMENDER SYSTEM BERBASIS METODE WEIGHTED SUM DAN PARETO FRONT UNTUK MANAJEMEN SUMBER DAYA AIR - Putri, Astrid Novita (Jurusan Teknik Informatika Fakultas Teknik Universitas Trunojoyo Madura, 2024)
AbstractClean water is used daily to meet individual needs such as cooking, drinking, bathing, and more. Clean water is essential to support human metabolism, which impacts health. However, obtaining clean water has become increasingly difficult due to high population growth and rising demand, coupled with limited availability.This study develops a multi-criteria recommender system model that considers various criteria or attributes to provide valuable recommendations, facilitating better decision-making based on suitable recommendations regarding water production and consumption. Using the Pareto front and weighted sum methods, this model balances trade-offs among criteria. The results of this study offer an optimal solution for both consumers and water resource management in Semarang City to achieve balance, with W1 minimizing water consumption and W2 maximizing production. The recommended optimal solution is W1 = 0.5 and W2 = 0.5, yielding water consumption of 1,064,910.4 m³/ha and production yield of 14,933,601 tons/ha. Other findings include W1 = 0.1 and W2 = 0.9, yielding water consumption of 11,115,920 m³/ha and production yield of 16,341,636 tons/ha. W1 = 0.4 and W2 = 0.6, yielding water consumption of 11,115,920 m³/ha and production yield of 16,341,636 tons/ha, W1 = 0.7 and W2 = 0.3, yielding water consumption of 10,649,104 m³/ha and production yield of 14,933,601 tons/ha.These outcomes indicate optimal solutions based on different weighting balances between consumption and production criteria.Keywords: Multi-criteria recommender system, pareto front, water resource management